PENGEMBANGAN1ALAT PERAGA IPA TERPADU MATERI SISTEM GERAK PADA MANUSIA MENGGUNAKAN BAHAN BEKAS UNTUK SISWA KELAS VIII SMP - Zurnita Zurnita; Eni Yulianti; Arista Ratih (BIOCOLONY, 2022)
The background1of this research is that teachers at SMP Negeri 42 Merangin have never developed an Integrated Science teaching aid for human movement systems made from used materials such as used books and others. Teachers use textbooks for the learning process. This study aims to develop integrated science teaching aids on human movement system materials by utilizing used materials for class VIII1students of junior high schools that are valid and practical.1This research uses the method of1the 4-D model, namely define, design, develop, disseminate. The research subjects consisted of 5 people validating the1feasibility of content, language, presentation and graphics. The practicality test was carried out by 1 science teacher and 18 students. The results of product research in the form of props for human movement systems from used goods which were declared valid by the palidator were proven by the results of the validator's assessment that the content feasibility averaged 82%, presentation averaged 92%, and graphics averaged 97% overall percentage average -average 90.3%, (very valid). The teaching aids have also been declared practical, the average of the teachers is 3.76 (very practical), obtained by the average of the students is 3.44 (practical), so that the motion system teaching aids have been declared valid and practical.